Insights into Early Language Development: An Investigation of Speech Acquisition in 25-Month-Old Toddler - Aprilia, Fitria; Neisya, Neisya (Universitas Pendidikan Mandalika, 2024)
This study delves into the early language development of a 25-month-old toddler, emphasizing phonological aspects encompassing consonants, vowels, and diphthongs. Conducted in Palembang in December 2023, the research employs a qualitative methodology utilizing a case study approach. The investigation aims to address the crucial role of phonological development in early language acquisition and its implications for linguistic theory and pedagogy. By focusing on the phonological repertoire of a toddler identified as